URGENSI AFILIASI INTELIGENSI (AI) DALAM DUNIA PENDIDIKAN PESANTREN HIDAYATUL MUBTADI’IN NGUNUT TULUNGAGUNG: URGENSI AFILIASI INTELIGENSI (AI) DALAM DUNIA PENDIDIKAN PESANTREN HIDAYATUL MUBTADI’IN NGUNUT TULUNGAGUNG - Muhammad Saiqul Huda; Muhammad Fathur Ro’uf; Moh Nashihudin (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
Abstract: Hidayatul Mubtadi’in Islamic Boarding School, Ngunut, Tulungagung as an Islamic education Institution requires innovative strategies to improve the quality of education. Artificial Intelligency (AI) is one strategy that can improve students’ abilities in facing global challenges. Artificial Intelligency (AI) is abranch of computer science that studies how to make computer act like humans, who can think, act and make decisions. This research aims to find out how important the role of Artificial Intelligency (AI) is in the wordld of education from various level to improve the quality of learning, especially at the Hidayatul Mubtadi’in Islamic Boarding School. The research methode uses a qualitative descriptive approuach with data collection techniques through questionnaires. The respondents of this reaserch were student from middle school, high school, and teachers from Sunan Gunung Jati Ngunut Tulungagung Middel School and High School. The research results show that the use of AI is really needed to make learning more enjoyable, the uses of AI makes it easier for student to understand teaching material, the uses of AI is very necessary in the learning process, the use of AI can be applied to the learning process. Therefore, AI is an urgent strategy to improve the quality of education at the Hidayatul Mubtadi’in Islamic Boarding School.